# Activities 9

### 9.1

Solve the equations by graphing:

a)
$\begin{array}{ccc}\hfill I\phantom{\rule{0.22em}{0ex}}\phantom{\rule{0.22em}{0ex}}-3x-5y& =-30\hfill & \hfill \\ \hfill II\phantom{\rule{0.22em}{0ex}}\phantom{\rule{0.22em}{0ex}}-x-5y& =-10\hfill \end{array}$
b)
$\begin{array}{ccc}\hfill I\phantom{\rule{0.22em}{0ex}}\phantom{\rule{0.22em}{0ex}}-x-4y& =-8\hfill & \hfill \\ \hfill II\phantom{\rule{0.22em}{0ex}}\phantom{\rule{0.22em}{0ex}}-2x+y& =-7\hfill \end{array}$
c)
$\begin{array}{ccc}\hfill I\phantom{\rule{0.22em}{0ex}}\phantom{\rule{0.22em}{0ex}}-2x-y& =-7\hfill & \hfill \\ \hfill II\phantom{\rule{0.22em}{0ex}}\phantom{\rule{0.22em}{0ex}}-2x+y& =-1\hfill \end{array}$
d)
$\begin{array}{ccc}\hfill I\phantom{\rule{0.22em}{0ex}}\phantom{\rule{0.22em}{0ex}}-2x+y& =4\hfill & \hfill \\ \hfill II\phantom{\rule{0.22em}{0ex}}\phantom{\rule{0.22em}{0ex}}x+y& =4\hfill \end{array}$

### 9.2)

Solve the equations with the substitution method:

a)
$\begin{array}{ccc}\hfill I\phantom{\rule{0.22em}{0ex}}\phantom{\rule{0.22em}{0ex}}-2x-5y& =-30\hfill & \hfill \\ \hfill II\phantom{\rule{0.22em}{0ex}}\phantom{\rule{0.22em}{0ex}}-2x+y& =-6\hfill \end{array}$
b)
$\begin{array}{ccc}\hfill I\phantom{\rule{0.22em}{0ex}}\phantom{\rule{0.22em}{0ex}}-x-y& =-4\hfill & \hfill \\ \hfill II\phantom{\rule{0.22em}{0ex}}\phantom{\rule{0.22em}{0ex}}-6x+y& =-38\hfill \end{array}$
c)
$\begin{array}{ccc}\hfill I\phantom{\rule{0.22em}{0ex}}\phantom{\rule{0.22em}{0ex}}3x-2y& =18\hfill & \hfill \\ \hfill II\phantom{\rule{0.22em}{0ex}}\phantom{\rule{0.22em}{0ex}}x+y& =16\hfill \end{array}$
d)
$\begin{array}{ccc}\hfill I\phantom{\rule{0.22em}{0ex}}\phantom{\rule{0.22em}{0ex}}2x-y& =-3\hfill & \hfill \\ \hfill II\phantom{\rule{0.22em}{0ex}}\phantom{\rule{0.22em}{0ex}}3x+y& =18\hfill \end{array}$

### 9.3)

Solve the equations with the elimination method:

a)
$\begin{array}{ccc}\hfill I\phantom{\rule{0.22em}{0ex}}\phantom{\rule{0.22em}{0ex}}-x-3y& =-23\hfill & \hfill \\ \hfill II\phantom{\rule{0.22em}{0ex}}\phantom{\rule{0.22em}{0ex}}x+y& =-3\hfill \end{array}$
b)
$\begin{array}{ccc}\hfill I\phantom{\rule{0.22em}{0ex}}\phantom{\rule{0.22em}{0ex}}-x+y& =-1\hfill & \hfill \\ \hfill II\phantom{\rule{0.22em}{0ex}}\phantom{\rule{0.22em}{0ex}}-3x+y& =-7\hfill \end{array}$
c)
$\begin{array}{ccc}\hfill I\phantom{\rule{0.22em}{0ex}}\phantom{\rule{0.22em}{0ex}}-2x+y& =-6\hfill & \hfill \\ \hfill II\phantom{\rule{0.22em}{0ex}}\phantom{\rule{0.22em}{0ex}}-x-3y& =-17\hfill \end{array}$
d)
$\begin{array}{ccc}\hfill I\phantom{\rule{0.22em}{0ex}}\phantom{\rule{0.22em}{0ex}}-x+y& =4\hfill & \hfill \\ \hfill II\phantom{\rule{0.22em}{0ex}}\phantom{\rule{0.22em}{0ex}}x+9y& =46\hfill \end{array}$

You can find the solutions here.